Pengenalan Media Pembelajaran Online Kreatif Di Tengah Pandemi Covid-19 Pada Panti Asuhan Putri Aisyiyah Wilayah Riau - Norra Isnasia Rahayu; Sri Rahmayanti; Siti Hanifa Sandri; Hendri Ali Ardi; Bakaruddin Bakaruddin; Misral Misral; Jeki Algustri (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The target of the training activity is the young women of the Aisyiyah Women's Orphanage. Children are expected to be able to increase their insight and ability to understand learning in online teaching and learning activities. Although specifically the problem for orphanage children is the weakness of strengthening the ability to master learning materials quickly (Quantum Learning) and soft skills. In addition, this activity can also motivate orphanage children to be more creative, innovative and independent. This community service activity method uses the lecture method by the presenters and direct demonstrations are practiced by the participants, as well as a question and answer session. The introduction of creative online learning media using the Google Classroom application is very inspiring in learning and teaching innovation. By mastering a number of new skills by trainees, it will also have an impact on increasing learning achievement in schools which are now carried out online